Special education international perspectives practices across the globe - Bakken, Jeffrey P. (Advances in special education ;, 2014)
The volume provides a comprehensive discussion of special education from across the globe. The volume includes chapters from major countries such as United States, Canada, United Kingdom, Russia and Japan as well as countries such as Nigeria, Israel and Pakistan. Discussions related to these countries will include information on origins of special education specific to that country, prevalence and incidence rates, trends in legislation and litigation, educational interventions, working with families, teacher training, a perspective on the progress of special education, and challenges that remain.